(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
When speaking about innovation in education and teaching, people usually refer to changes fostered by innovation in technology for the purpose of learning, teaching, and curriculum development. The reason why this happens is obvious: technical / technological changes do happen fast and their effects are more spectacular than the effects induced by the slower, but longer lasting institutional innovation. One of the most important such innovation that occurred in Europe, in the last decades, is the Bologna Process. Its relevance is given, beneath encouraging mobility, mainly by opening the possibility of standardization and commensurability for the European national Higher Education systems. European nation-states do consider education one of the main territories of national sovereignty, sometimes even by raising artificial barriers in the way of rapprochement. In my paper, I intend to present the main advantages of the Bologna Process, the art it gained ground in Europe and the main dangers lurking on it, especially nationalist populism. As an illustration, I will use the case of Hungary, one of the member-states with the most ambiguous attitudes towards the EU and its integration process. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.